Business-IT Alignment: A practical research approach - Suwatana Charoensuk (2018)
© 2014 Elsevier Inc. The purpose of this study is to empirically investigate the impact of Business-Information Technology Alignment, or BIA, on organizations and to revisit the BIA antecedents by using data from hotel sector of the service industry. The research model was developed based on the literature and inputs from the hotel industry and IT experts, using the Structural Equation Modeling (SEM) technique in data analysis, and data from phone interviews that were conducted with both business and IT personnel from 3 to 5 star hotels in Thailand. We found that Business-IT Alignment does have a positive relationship with organizational performance. Shared domain knowledge was found to have the highest relationship with Business-IT Alignment while IT management sophistication had the least impact, but in a negative direction, while organizational size was found to be a moderator. Other BIA antecedents were effective communication, IT operational and implementation success, and planning sophistication. This study developed a model that integrates the alignment between the strategic and operational levels which offers a holistic view of BIA, different from previous studies that considered only one or the other level. Secondly, we cross verify the antecedents from the literature and actual practice by interviewing experts in the industry. Finally, we revisited measurements and relationships among the constructs so that the model is up-to-date and applicable to the current business environment.